One-pot bioconversion of tomato waste into poly-gamma-glutamic acid (gamma-PGA) biopolymer by a novel biocatalyst - Nair, Pranav G.; Joseph, Emmanuel; Killi, Naresh; Konchada, Sravanya; Nisal, Anuya; Gundloori, Rathna Venkata Naga; Dharne, Mahesh S. (ACS Sustainable Chemistry & Engineering, 2021)
Landfilling of rotten tomatoes can lead to environmental instability and a huge economic loss to the producers. This letter reports an effective valorization of tomato waste into a promising biopolymer, i.e., poly-gamma-glutamic acid (gamma-PGA) by a novel biocatalyst Bacillus paralicheniformis NCIM 5769. The gamma-PGA is one of the most expensive biopolymers with multifarious applications in wound healing, drug delivery, and regenerative medicine fields. However, its adoption into various applications is finite due to its exorbitant production cost. Herein, rotten tomatoes (without additional nutrient supplementation) served as the chassis for the fermentative production of 40 g/L of highly pure gamma-PGA within 48 h at ambient temperature. Further, NMR, DSC, and TGA confirmed the purity of synthesized gamma-PGA identical to standard gamma-PGA. This process has potential in the commercialization of.-PGA by significantly reducing the production cost, followed by the effective utilization of tomato waste leading to United Nations Sustainable Development Goal 12 (i.e., ensure sustainable consumption and production patterns).
Keywords: Commercialization; Poly-gamma-glutamic acid; Rotten tomatoes; United Nations Sustainable Development Goals; Waste utilization

Poly-gamma-glutamic acid biopolymer: a sleeping giant with diverse applications and unique opportunities for commercialization - Nair, Pranav; Navale, Govinda R.; Dharne, Mahesh S. (Biomass Conversion and Biorefinery, 2023)
Poly-gamma-glutamic acid (gamma-PGA) is a biodegradable, non-toxic, ecofriendly, and non-immunogenic biopolymer. Its phenomenal properties have gained immense attention in the field of regenerative medicine, the food industry, wastewater treatment, and even in 3D printing bio-ink. The gamma-PGA has the potential to replace synthetic non-degradable counterparts, but the main obstacle is the high production cost and lower productivity. Extensive research has been carried out to reduce the production cost by using different waste; however, it is unable to match the commercialization needs. This review focuses on the biosynthetic mechanism of gamma-PGA, its production using the synthetic medium as well as different wastes by L-glutamic acid-dependent and independent microbial strains. Furthermore, various metabolic engineering strategies and the recovery processes for gamma-PGA and their possible applications are discussed. Finally, highlights on the challenges and unique approaches to reduce the production cost and to increase the productivity for commercialization of gamma-PGA are also summarized.
Keywords: Commercialization; Multi-nutritious; Poly-gamma-glutamic acid; Waste valorization